2020
DOI: 10.1002/ajb2.1442
|View full text |Cite
|
Sign up to set email alerts
|

Cold tolerance in the genusArabidopsis

Abstract: Premise Cold tolerance is an important factor limiting the geographic distribution and growing season for many plant species, yet few studies have examined variation in cold tolerance extensively within and among closely related species and compared that to their geographic distribution. Methods This study examines cold tolerance within and among species in the genus Arabidopsis. We assessed cold tolerance by measuring electrolyte leakage from detached leaves in multiple populations of five Arabidopsis taxa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 74 publications
(128 reference statements)
2
21
0
Order By: Relevance
“…Cold‐acclimation is an adaptive process, which increases the freezing tolerance of plants. Without cold acclimation, plants exposed to freezing temperatures could be severely injured as a result of ice crystal formation in the apoplast causing membrane damage (Armstrong et al., 2020; Zhao et al., 2016). Electrolyte leakage assays have been previously used to assess the differences in freezing tolerance of Arabidopsis plants.…”
Section: Resultsmentioning
confidence: 99%
“…Cold‐acclimation is an adaptive process, which increases the freezing tolerance of plants. Without cold acclimation, plants exposed to freezing temperatures could be severely injured as a result of ice crystal formation in the apoplast causing membrane damage (Armstrong et al., 2020; Zhao et al., 2016). Electrolyte leakage assays have been previously used to assess the differences in freezing tolerance of Arabidopsis plants.…”
Section: Resultsmentioning
confidence: 99%
“…Collembolans used in the experiment originated from a population collected in Siena, Italy, in 2016 and thereafter maintained at 20°C, 70% RH and a photoperiod of 12:12 hour light: dark regime for ca. 15 generations (for details see [ 40 ]). During acclimation, 10–13 collembolans of unknown sex were held in 180 replicate petri dishes (55 mm) containing a water-saturated plaster-of-paris: charcoal (9:1) medium and an algae-covered twig was provided as food source.…”
Section: Methodsmentioning
confidence: 99%
“…However, findings on the relationship between the latitudinal origin of populations and the level of plasticity in thermal tolerance are generally contrasting for both arthropod and plant species. Some studies find no relationship between latitude and plasticity for animal ectotherm species [ 16 , 17 , 37 39 ] and plants [ 40 ]. Other studies have found such an association for cold [ 41 , 42 ] and heat tolerance [ 43 , 44 ] in animals and for cold [ 45 ], and heat tolerance [ 46 ] in plants.…”
Section: Introductionmentioning
confidence: 99%
“…An important adaptation of plants inhabiting cold-characterized regions is their ability to protect against frost damage induced by minimum winter temperatures through a process called cold acclimation. Minimum winter temperatures remain a major factor in determining species distribution ranges (Armstrong et al, 2020). Tolerance to freezing temperatures is a trait most common in temperate as well as arctic and alpine plants, which are frequently exposed to sub-zero temperatures, whereas most tropical and subtropical plants suffer injuries from temperatures below 10 °C (Xin & Browse, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Such changes include the accumulation of soluble sugars, which act as cryoprotectants for enzymes, prevent excessive dehydration, and promote membrane stability, as well as compositional and structural changes in the cell membrane (Reyez-Díaz et al, 2006;Uemura et al, 2006); cold acclimation is therefore clearly a multifactorial process in which many genes act in parallel to ensure maximum freezing tolerance (Renaut et al, 2005). There is natural variation in the freezing tolerances of different plants and their potential to acquire and increase tolerance following cold acclimation; this variation exists among species and even populations within species (Xin & Browse, 2000;Hannah et al, 2006); Some of this variation may be linked to the species' or populations' distribution (Armstrong et al, 2020). Varying environmental conditions in different geographic regions may expose plants to different selection pressures, which may lead to differences in phenotypic adaptation to cold in geographically distant populations (Zuther et al, 2012).…”
Section: Introductionmentioning
confidence: 99%